Relevant Facts from Aerosol Measles Vaccine Studies - Jorge, Fernández de Castro; Garcia-Garcia, M. L.; Diaz-Ortega, Jose L.; Castaneda, Deyanira (Scientific Research, 2016)
Most of the facts regarding measles aerosol vaccination have been quite thoroughly dealt with in the book by S. Plotkin, Mass Vaccination: Global Aspects—Progress and Obstacles (2006 Ed) [1]. However, there are some aspects mentioned there that should perhaps have been emphasized more strongly and others that have emerged as relevant issues since then. We shall start with the quite important point that in the Sabin et al. [2] first study made in Monterrey, N. L., México [3], antibody reaction for recipients of respiratory-route Edmonston-Zagreb vaccines was not fully developed (100%) until six months after aerosol inhalation. At six weeks, only 90% had increased blood levels of antibody, a fact for which there is no easy explanation, but one which should be considered when dealing with serologic evaluation of measles vaccines given by aerosol in which shortterm results less than encouraging. Results of the second study performed by Sabin et al. in Monterrey [2] establish that the percentage of sero-responses is directly dose-dependent. In turn, the dose itself depends on at least three facts: 1) concentration of virus in the vaccine used; 2) kind of nebulizer used; and 3) time of exposure. Another point to be stressed is that the vaccine used in the first trials [1]-[3], as well in the aerosol mass vaccination in México, though originally the Ickic strain attenuated in HDP, was also grown for final harvesting in HDP (MRC-5), whereas current Edmonston-Zagreb vaccines are obtained by final culture in chick embryo fibroblasts that provide 1 log more final product, more beneficial from an economic point of view, but not for adaptation to human tissues. A crucial consideration in aerosol measles mass campaigns is the lack of electricity/energy supply, particularly in rural communities. To deal with these issues, a rudimentary assembly was utilized to produce the aerosol for mass vaccinations performed during the serious Mexican epidemic of 1990-1991: a tire pump connected to a Clay-Adams nebulizer. As this equipment works only with direct current, a car battery was used to supply sufficient energy to vaccinate thousands of children.
Keywords: Immunology Immunopharmacology